2008
DOI: 10.4323/rjlm.2008.245
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenesis imperfecta: forensic assessment of traumatic injuries. Case report and literature review

Abstract: A 39 years old male with osteogenesis imperfecta type I presented to an emergency clinic accusing pain and movement limitations in his left arm appeared after a traumatic event. Clinical and radiological examinations revealed a fracture of the distal end of his left humerus, but also an underlying pathologic condition: osteogenesis imperfecta. Osteogenesis imperfecta patients may represent a chalange for forensic evaluation, particularly when trying to differentiate between spontaneous and traumatic fractures.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…An important issue when aortic dissection is found at the autopsy is the genetic screening, especially in young persons with Erdheim lesions (cystic medionecrosis) were there are no other significant associated comorbidities (atherosclerosis, trauma, etc) [7,25,26]. Usually when a genetic predisposition exists, aortic dissection is associated with various genetic syndromes (Marfan -FBN-1 or TGFbR2 mutations [27], Ehlers-Danlos IV -COL3A1 [28], Turner -45XO [29][30][31], Noonan -PTPN11, KRAS, SOS1, RAF1 [30,31], osteogenesis imperfecta -CO1A1,COL1A2 [32], homocystinuria -CBS [31], AD-PKD -PKD1, PKD2 [31], pseudoxanthoma elasticum, Hurler syndrome, Loeys-Dietz syndrome [31], etc) with manifest phenotypes. Very unfrequently aortic dissection predisposition is determined by genes that aren't responsible for other clinical manifestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important issue when aortic dissection is found at the autopsy is the genetic screening, especially in young persons with Erdheim lesions (cystic medionecrosis) were there are no other significant associated comorbidities (atherosclerosis, trauma, etc) [7,25,26]. Usually when a genetic predisposition exists, aortic dissection is associated with various genetic syndromes (Marfan -FBN-1 or TGFbR2 mutations [27], Ehlers-Danlos IV -COL3A1 [28], Turner -45XO [29][30][31], Noonan -PTPN11, KRAS, SOS1, RAF1 [30,31], osteogenesis imperfecta -CO1A1,COL1A2 [32], homocystinuria -CBS [31], AD-PKD -PKD1, PKD2 [31], pseudoxanthoma elasticum, Hurler syndrome, Loeys-Dietz syndrome [31], etc) with manifest phenotypes. Very unfrequently aortic dissection predisposition is determined by genes that aren't responsible for other clinical manifestation.…”
Section: Discussionmentioning
confidence: 99%
“…The genes responsible for non-Syndromic aortic aneurysm and dissection are TAAD1 [33], FAA1 [34], TAAD2 [35], MYH11 [36]; other possible candidates are FBLN2, TIMP4, MMP3, COL1A1, COL1A2 [31,32]; if they are detected in a patient with aortic dissection genetic counseling must be given to their families.…”
Section: Discussionmentioning
confidence: 99%
“…The first being whether this child presenting with an unexplained fracture is a victim of battered child syndrome or not since fractures in various parts of the skeletal system are one of the most frequent manifestations of this syndrome after skin injuries. Differentiating these two conditions, although sometimes challenging, is very crucial, and misdiagnosing one for another can have a psychological, social, and medical impact on the patients and families and further judicial complications [ 25 - 26 ].…”
Section: Reviewmentioning
confidence: 99%
“…Second, healing time: although in osteogenesis imperfecta, the healing time is not significantly different from normal people, prolonged immobilization following a fracture is of clinical necessity since the complication rate is higher than in normal people. And finally, complication rate: patients with osteogenesis imperfecta have higher rates of developing joint stiffness and early arthritic changes, which results in a significantly higher incidence of pain [ 25 ].…”
Section: Reviewmentioning
confidence: 99%
“…In Romania our previous studies revealed that the most often find accusations are ommisive (usually associated with surgical specialties) and commisive (in both surgical and medical specialties) [10][11][12][13]. Another classification divides medical errors according to their type in dolosive (molest, insult, defamation, outrage), by negligence, superficiality, against medical humanity, against common caution, ignorance, incompetence, refusal to treat, refusal to answer to a request to treat, patient abandon, etc.…”
mentioning
confidence: 99%